2019
DOI: 10.1108/ci-07-2019-0064
|View full text |Cite
|
Sign up to set email alerts
|

Demystifying the concept of offsite manufacturing method

Abstract: Purpose This study aims to develop a more inclusive working definition and a formalised classification system for offsite construction to enable common basis of evaluation and communication. Offsite manufacturing (OSM) is continuously getting recognised as a way to increase efficiency and boost productivity of the construction industry in many countries. However, the knowledge of OSM varies across different countries, construction practices and individual experts thus resulting into major misconceptions. The l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 36 publications
(62 reference statements)
0
19
0
Order By: Relevance
“…As a result, the classification of OSC engineering-method framework is adopted to be product oriented. This classification is inspired by a recent comprehensive study on OSC by Ayinla et al (2019).…”
Section: Osc Engineering-methods Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the classification of OSC engineering-method framework is adopted to be product oriented. This classification is inspired by a recent comprehensive study on OSC by Ayinla et al (2019).…”
Section: Osc Engineering-methods Frameworkmentioning
confidence: 99%
“…Each of the proposed maturity scales are modified from Ayinla et al (2019) except that of the industrial design.…”
Section: Osc Engineering-methods Maturity Modelsmentioning
confidence: 99%
“…OSM classification is still unfolding [40,41], including taxonomy and links with industry foundations classes (IFC) for example. The Housing Forum [15] guide indicated that several proposals aimed to encourage manufacturers to offer their systems through international and accessible standards such as publicly available specifications (PAS), etc.…”
Section: Off-site Manufacturing Within Aecmentioning
confidence: 99%
“…In particular, with regard to methods of promoting and evaluating innovation in public tenders, research on methods of inducing innovation at bidders using a bridge construction project as a subject (Lenderink et al, 2020), methods of building process innovation through a consortium of universities and industry (Lavikka et al, 2020) have been discussed. In addition, in research at the level of firm behaviour, a survey of the definition and classification of off-site construction methods (Ayinla et al, 2019), the role of innovation brokers (Sergeeva and Liu, 2019) and the role and evaluation of iContract, an intelligent contracting technology (McNamara and Sepasgozar, 2020), a review of the use of VR to facilitate communication (Wen and Gheisari, 2020), technology management systems and practical guidance for physical-mechanical robotic systems (Linner et al, 2020), building information modelling (BIM), a review of public client initiatives on demonstrations (Lindblad and Gustavsson, 2021). And, in-depth research based on questionnaires and interviews with experts has been conducted, on real-world and impact studies on loosely coupled systems in construction (Sandberg et al, 2020), theories and case studies on the contribution of tact production to construction production flow (Lehtovaara et al, 2021), on lean procurement readiness (Suresh and Arun Ram Nathan, 2020), a discussion on barriers to adoption of building information modelling in small and medium-sized enterprises (SMEs) (Saka and Chan, 2020), an examination of lean building surveying services from a waste reduction perspective (Khan (Khan and Ali, 2020) and a study on collaborative procurement methods to mitigate claims and disputes (Elhag et al, 2020).…”
Section: Recent Prior Researchmentioning
confidence: 99%